1997
DOI: 10.1007/bf02506847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic position of podostemaceae, a marvelous aquatic flowering plant family

Abstract: Podostemaceae are aquatic herbs and are famous for their anomalous vegetative morphology, occurring only in rapids. Because of its peculiar morphology, there were no established theory nor accepted opinion on the phylogenetic position. Especially, Cusset and Cusset (1988) proposed the new class, Podostemopsida beside the Magnollopsida and Liliopsida. We, therefore, consequences extensive and detailled analyses using nucleotide sequences ofrbcL genes for two genera and three species of the family together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…The Podostemaceae as molecular misfits-The Podostemaceae have to be regarded as morphological misfits (Bell, 1991;Rutishauser, 1995Rutishauser, , 1997. Meanwhile, molecular data for various Podostemaceae genera were presented by Les, Philbrick, andNovelo (1997, 1998), as well as Ueda et al (1997). Similar to Ceratophyllaceae (Qiu et al, 1993;Sytsma and Baum, 1996) the Podostemaceae turn out to be molecular misfits as compared to other angiosperms.…”
Section: Molecular and Nonmolecular Criteria Elucidating The Phylogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The Podostemaceae as molecular misfits-The Podostemaceae have to be regarded as morphological misfits (Bell, 1991;Rutishauser, 1995Rutishauser, , 1997. Meanwhile, molecular data for various Podostemaceae genera were presented by Les, Philbrick, andNovelo (1997, 1998), as well as Ueda et al (1997). Similar to Ceratophyllaceae (Qiu et al, 1993;Sytsma and Baum, 1996) the Podostemaceae turn out to be molecular misfits as compared to other angiosperms.…”
Section: Molecular and Nonmolecular Criteria Elucidating The Phylogenmentioning
confidence: 99%
“…Fossil evidence, however, is lacking for the Podostemaceae. In spite of the problem of long-branch attraction, Les, Philbrick, and Novelo (1997) as well as Ueda et al (1997) agree that it is best to accept the Crassulaceae, Haloragaceae, and even Hydrostachyaceae as sister groups of the Podostemaceae. This coincides with the classical view that the Podostemaceae belong to the Rosidae clade (Warming, 1890;Engler, 1930;van Royen, 1951).…”
Section: Molecular and Nonmolecular Criteria Elucidating The Phylogenmentioning
confidence: 99%
“…Due to these ecological and morphological specializations, the phylogenetic relationships of Podostemaceae have long been controversial. Chloroplast rbcL sequence data deduced a phylogenetic relationship of Podostemaceae with Crassulaceae (Les et al, 1997 [24] ; Ueda et al, 1997 [44] ). By contrast, recent analyses of 18S rDNA alone, combined data of 18S rDNA/rbcL, and 18S rDNA/rbcL/atpB sequences for a great number of members of families including Crassulaceae suggested that Podostemaceae belong to a Malpighiales clade (Soltis et al, 1999 [36] , 2000 [37] ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and molecular data indicate that the Podostemaceae with their unique architecture are dicotyledons related to the Rosids (e.g. Malpighiales clade) within the Eudicots (Les, Philbrick & Novelo, 1997;Ueda et al, 1997;Soltis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%